3D Graphene-Nickel Hydroxide Hydrogel Electrode for High-Performance Supercapacitor. (1st April 2016) - Mao, Lu; Guan, Cao; Huang, Xiaolei; Ke, Qingqing; Zhang, Yu; Wang, John
Highlights: An adsorption-hydrothermal strategy is adopted for the first time for the in-situ integration of 3D hydrogel of NG/Ni(OH)2 nanocomposite. The 3D nanocomposite hydrogel thus obtained is explored as the monolithic free-standing supercapacitor electrode without adding any other binders or conductive additives. High specific capacitances of 782 F g −1 and 1748 F g −1 based on the mass of Ni(OH)2 alone are achieved for the nanocomposite hydrogel. High capacitance retention as well as excellent cycling stability are demonstrated. Abstract: 3D graphene-based frameworks with interpenetrating macroporous structures have attracted great interests recently since they can serve as robust matrix for accommodating guest nanoparticles for use in a wide range of applications. Here, an adsorption-hydrothermal strategy is adopted for the in-situ growth of Ni(OH)2 nanoplates using three dimensional (3D) nitrogen-containing graphene hydrogel (NG) as the substrate. The NG/Ni(OH)2 nanocomposite hydrogel thus obtained is explored as the monolithic free-standing supercapacitor electrode without adding any other binders or conductive additives. The 3D hierarchical structure of the NG/Ni(OH)2 nanocomposite can not only provide a large accessible surface area, but also facilitate ion diffusion and charge transport for much improved supercapacitive performance. The gel with Ni(OH)2 loading of ∼40% achieves a high specific capacitance of 782 F g −1  at the current density of 0.2 A g −1, which equals to a specific capacitance of 1748 F g −1 based on the mass of Ni(OH)2 alone. Excellent cycling stability of only 10% capacitance loss after 10000 cycles is also achieved due to the robust adhesion between the metal hydroxide and nitrogen containing graphene. Furthermore, high capacitance retention of ∼80% can be achieved when the current density is increased 100 fold from 0.2 to 20 A g −1 .